Single Amino Acid Substitution in the DNA Repairing Gene Radiation-Sensitive 4 Contributes to Ultraviolet Tolerance of a Plant Pathogen - Wang, Yan-Ping; Yang, Li-Na; Feng, Yuan-Yuan; Liu, Songqing; Zhan, Jiasui (Frontiers in Microbiology, 2022)
To successfully survive and reproduce, all species constantly modify the structure and expression of their genomes to cope with changing environmental conditions including enhanced ultraviolet (UV) radiation. Thus, knowledge of species adaptation to environmental changes is a central theme of evolutionary studies which could have important implication impacts for disease management and social-ecological sustainability in the future but is generally insufficient. Here, we investigated the evolution of UV adaptation of organisms by population genetic analysis of sequence structure, physiochemistry, transcription and fitness variation in the radiation sensitive 4 (RAD4) gene of the Irish potato famine pathogen Phytophthora infestans sampled from various altitudes. We found RAD4 is a key gene determining resistance of the pathogen to UV stress as indicated by strong phenotype-genotype-geography associations and up-regulated transcription after UV exposure. We also found conserved evolution in the RAD4 gene. Only five nucleotide haplotypes corresponding to three protein isoforms were detected in the 140 analyzed sequences and mutations were constrained to the N-terminal domain of the protein. Physiochemical changes associated with nonsynonymous mutations generate severe fitness penalty to mutants, which are purged out by natural, leading to the observed conserved evolution of the gene.